Association between serum uric acid‐to‐high‐density lipoprotein cholesterol ratio and insulin resistance in an American population: A population‐based analysis - Zhou, Xiaohai; Xu, Jing (Journal of diabetes investigation, 2024)
ABSTRACT Introduction Previous studies have demonstrated a correlation between the serum uric acid‐to‐high‐density lipoprotein cholesterol ratio (UHR) and insulin resistance (IR) in individuals with type 2 diabetes mellitus. However, no existing studies have investigated the relationship between IR and UHR in the general population. Therefore, the primary objective of this study was to investigate the correlation between UHR and IR in the general American population. Methods A sample of 8,817 participants was selected from the 2013 to 2020 National Health and Nutrition Examination Survey (NHANES). Homeostatic model assessment of insulin resistance (HOMA‐IR) was used to assess insulin resistance. Multiple logistic regression, generalized smooth curve fitting, and subgroup analysis were used to assess the association between IR and UHR. Results Multiple logistic regression analysis indicated a significant correlation between insulin resistance and UHR, with odds ratios (OR) of 1.07 (95% CI = 1.03–1.11) in males and 1.18 (95% CI = 1.13–1.25) in females. A non‐linear relationship and saturation effect between IR risk and UHR were observed, characterized by an inverted L‐shaped curve and a critical inflection point at 8.82. It was found that the area under the ROC curve (AUC) of UHR was significantly larger (AUC = 0.703 for males and 0.747 for females, all P < 0.01) compared with the use of UA or HDL‐C alone. Subgroup analysis showed that this independent association remain consistent regardless of race, age, BMI, diabetes, moderate activities, education level, alcohol drinking, and gender. Conclusion Elevated UHR demonstrates a significant correlation with insulin resistance, so it can be used as a potential indicator of insulin resistance within the American population. Elevated UHR demonstrates a significant association with insulin resistance within the American population. UHR is more effective in detecting IR compared with the use of HDL‐C or UA alone. A non‐linear association between IR risk and UHR was discovered.